2018
DOI: 10.4102/sajhivmed.v19i1.770
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and co-morbidities associated with changes in renal function among antiretroviral treatment-naïve adults in South Africa: A chart review

Abstract: IntroductionOur systematic scoping review has demonstrated a research gap in antiretroviral treatment (ART) nephrotoxicity as well as in the long-term outcomes of renal function for patients on ART in South Africa. Bearing in mind the high prevalence of human immunodeficiency virus (HIV) in South Africa, this is of great concern.ObjectivesTo determine the risk factors and co-morbidities associated with changes in renal function in HIV-infected adults in South Africa.MethodsWe conducted a retrospective study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
6
6
0
Order By: Relevance
“…We also found a low prevalence of renal impairment among study participants. is finding was consistent with findings in South Africa (7.6%) [13] and Malaysia 9.3% [17], lower than in Korean (14.4%) [22] and Japan (22.1%) [12], and higher than in Spain (4-5%) [23].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We also found a low prevalence of renal impairment among study participants. is finding was consistent with findings in South Africa (7.6%) [13] and Malaysia 9.3% [17], lower than in Korean (14.4%) [22] and Japan (22.1%) [12], and higher than in Spain (4-5%) [23].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, renal impairment was defined as eGFR less than 60 ml/min/1.73 m 2 [13]. In the univariate analysis, we used Chi-squared and Fisher's exact tests to assess bivariate relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to HIV viremia, chronic inflammation, and potentially nephrotoxic antiretroviral drugs, as well as structural or functional disorders in the context of ageing and associated comorbidities may play a role in the pathogenesis of eGFR decline in HIV-infected patients on ART [ 23 , 43 ]. However, an improvement in eGFR after the commencement of ART has been demonstrated in the Tanzanian, South African and Ugandaian cohort studies [ 20 , 21 , 32 ]. Our results also showed that among patients with baseline normal renal function (eGFR ≥90 ml/min/1.73 m 2 ), 49.7% experienced some degree of renal impairment, which is similar to recent studies done in Tanzania and China [ 29 , 33 ].…”
Section: Discussionmentioning
confidence: 99%